Psychiatric morbidity in epilepsy - Singh, Prem; Pandey, Achyut K. (International Journal of Research in Medical Sciences, 2017)
Background: Psychiatric morbidity occurs more frequently in patients with epilepsy than in the general population. Routine evaluation and treatment of psychiatric morbidity can be helpful in improving epilepsy care but such data are relatively meagre from developing countries. Methods: The study was conducted in the Epilepsy Clinic of Department of Neurology at a tertiary care hospital over a period of one year.101 patients were included after fulfilling the inclusion criteria. All the patients seeking treatment in the OPD were screened, assessed and then all procedures were fully explained to them. History regarding name, age sex, socio-demographic profile and detailed history regarding seizure disorder was taken from both the patient and the reliable informant. Bengali version of SRQ-24 was used to screen for psychiatric morbidity. Results: One hundred and one patients with epilepsy consisting of 70 men (69.3%) and 31 women (30.7%) were included. Their ages ranged from 15 to 52, the mean age being 26.17 (SD = 7.84). Out of the 101 patients, 65 patients (64.4%) were suffering from partial epilepsies and 36 patients (35.6%) were suffering from generalized epilepsies. 50.49% of the subjects screened positive for psychiatric morbidity. Psychiatric morbidity was higher in unmarried, unemployed males from rural background who were suffering from generalized epilepsy and taking multiple antiepileptic medications. Psychiatric morbidity was statistically significant in people with poor education and those born at home (p<0.05) as compared to well educated, institutionally born persons. Conclusions: 50.49% of the subjects screened positive for psychiatric morbidity.